2020
DOI: 10.3390/w12072040
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison and Validation of Saturated Hydraulic Conductivity Models

Abstract: Saturated hydraulic conductivity (Ksat) is fundamental to shallow groundwater processes. There is an ongoing need for observed and model validated Ksat values. A study was initiated in a representative catchment of the Chesapeake Bay Watershed in the Northeast USA, to collect observed Ksat and validate five Ksat pedotransfer functions. Soil physical characteristics were quantified for dry bulk density (bdry), porosity, and soil texture, while Ksat was quantified using piezometric slug tests. Average bdry and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 66 publications
3
50
1
Order By: Relevance
“…EF greater or equal to 0.5 indicated high performance for the evaluated PTFs. The PTF that has the highest EF value was the best performing function [8,21].…”
Section: Discussionmentioning
confidence: 99%
“…EF greater or equal to 0.5 indicated high performance for the evaluated PTFs. The PTF that has the highest EF value was the best performing function [8,21].…”
Section: Discussionmentioning
confidence: 99%
“…Hydraulic conductivity is the key factor of water flow through the substrate and it is affected by in-situ structure and pore volume [34]. Particularly, saturated hydraulic conductivity (Ks) is used to describe the movement of water through saturated soils and is a critical component in a resource management decision such as water conservation and irrigation systems [35]. Saturated hydraulic conductivity has been measured from undisturbed representative soils samples and volcanic deposits taken directly from selected outcrops.…”
Section: Hydraulic Conductivitymentioning
confidence: 99%
“…Further, increased water consumption by human activities was largely mitigated by evapotranspiration savings from deforestation, a practice that can no longer be sustained. Finally, Gootman et al [16] conducted a study validating five saturated hydraulic conductivity (K sat ) pedotransfer functions in a catchment of the Chesapeake Bay Watershed, Northeast United States. The study showed that dry bulk density and porosity were significantly different by location (p < 0.05) and four different models corroborated that spatial variability in farm-scale K sat estimates was small (CV < 0.5), thereby validating the use of simple, soil-property-based models to predict K sat , thereby increasing model applicability and transferability.…”
Section: Experimental Study Designs and Modelingmentioning
confidence: 99%